Analisis Permasalahan Pembelajaran Pendidikan Jasmani Melalui Zoom Meeting di SMAN 1 Rengasdengklok - Ahmad Mahirdo Holis; Resty Gustiawati; Febi Kurniawan (Universitas Singaperbangsa, 2021)
This study aims to find out the problems that are being faced by students when learning PJOK at school where the online system uses the zoom meeting application during the Covid-19 pandemic in class XII SMA Negeri 1 Rengasdengklok. The research method used in this research is qualitative. The subjects used were 30 students of class XII SMA Negeri 1 Rengasdengklok randomly. The results of this study indicate that 1) various online learning activities use zoom even though they are used side by side with other applications such as google meet, Google Drive, and WhatsApp and sometimes the signal is not good enough and the internet quota is sometimes inadequate. 2) students are less enthusiastic when learning through the zoom meeting application 3) in online learning through zoom meetings in physical education learning becomes less effective because it is not accompanied by the teacher directly and does not practice directly in the field.